Integrin-Linked Kinase Reduces H3K9 Trimethylation to Enhance Herpes Simplex Virus 1 Replication - Tsai, Meng-Shan; Chen, Shun-Hua; Chang, Chih-Peng; Hsiao, Yi-Ling; Wang, Li-Chiu (Frontiers in Cellular and Infection Microbiology, 2022)
Histone modifications control the lytic gene expression of herpes simplex virus 1 (HSV-1). The heterochromatin mark, trimethylation of histone H3 on lysine (K) 9 (H3K9me3), is detected on HSV-1 genomes at early phases of infection to repress viral gene transcription. However, the components and mechanisms involved in the process are mostly unknown. Integrin-linked kinase (ILK) is activated by PI3K to phosphorylate Akt and promote several RNA virus infections. Akt has been shown to enhance HSV-1 infection, suggesting a pro-viral role of ILK in HSV-1 infection that has not been addressed before. Here, we reveal that ILK enhances HSV-1 replication in an Akt-independent manner. ILK reduces the accumulation of H3K9me3 on viral promoters and replication compartments. Notably, ILK reduces H3K9me3 in a manner independent of ICP0. Instead, we show an increased binding of H3K9 methyltransferase SUV39H1 and corepressor TRIM28 on viral promoters in ILK knockdown cells. Knocking down SUV39H1 or TRIM28 increases HSV-1 lytic gene transcription in ILK knockdown cells. These results show that ILK antagonizes SVU39H1- and TRIM28-mediated repression on lytic gene transcription. We further demonstrate that ILK knockdown reduces TRIM28 phosphorylation on serine 473 and 824 in HSV-1-infected cells, suggesting that ILK facilitates TRIM28 phosphorylation to abrogate its inhibition on lytic gene transcription. OSU-T315, an ILK inhibitor, suppressed HSV-1 replication in cells and mice. In conclusion, we demonstrate that ILK decreases H3K9me3 on HSV-1 DNA by reducing SUV39H1 and TRIM28 binding. Moreover, our results suggest that targeting ILK could be a broad-spectrum antiviral strategy for DNA and RNA virus infections, especially for DNA viruses controlled by histone modifications.